Enhancing well-being in higher education: the role of job satisfaction and resilience among ELT instructors - Zaimoğlu, Senem; Dağtaş, Aysun (Frontiers in Psychology, 2025)
IntroductionAs academic demands intensify and institutional pressures increase, university-level English Language Teaching (ELT) instructors face growing risks to their psychological well-being. Understanding the factors that contribute to their well-being is essential for ensuring sustainable professional engagement. This study investigates the role of job satisfaction and teacher resilience in promoting psychological well-being among ELT instructors in higher education settings.MethodsA quantitative research design was employed, involving 173 ELT instructors working at universities in Türkiye. Data were collected through three validated instruments: the Teacher Job Satisfaction Scale, the Teacher Resilience Scale, and the Psychological Well-Being Scale. Multiple regression analyses were used to explore the predictive relationships among the variables.ResultsFindings revealed that both job satisfaction and resilience significantly and positively predicted psychological well-being. Among the two, job satisfaction emerged as the strongest predictor. In addition, teacher resilience was found to partially mediate the relationship between job satisfaction and psychological well-being.DiscussionThe results highlight the importance of fostering emotionally resilient and professionally satisfied ELT instructors. Institutional policies that enhance autonomy, promote professional development, and support well-being are critical for sustaining mental health and effective teaching performance in demanding higher education contexts.